2019
DOI: 10.1021/acs.jpclett.9b00764
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Transient Absorption Spectroscopy Elucidates Trapped-Hole Dynamics in CdS and CdSe Nanorods

Abstract: Charge-carrier traps play a central role in the excited-state dynamics of semiconductor nanocrystals, but their influence is often difficult to measure directly. In CdS and CdSe nanorods of nonuniform width, spatially separated electrons and trapped holes display relaxation dynamics that follow a power-law function in time that is consistent with a recombination process limited by trapped-hole diffusion. However, power-law relaxation can originate from mechanisms other than diffusion. Here we report transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(70 citation statements)
references
References 48 publications
9
61
0
Order By: Relevance
“…Additionally, a broad, minute positive amplitude was recorded for probe photon energies lower than 2.1 eV (600-750 nm, Figure S23), which builds up within the first ps. Previous studies attributed this spectral feature to the dissociation of excitons into electrons and holes with subsequent trapping of holes on the surface [46,68,69]. The subsequent behavior is characterized by the decay of the CdS bleach feature, accompanied by a small red-shift of the spectral position of the minimum of circa 50 meV, and the decay of the CdSe bleach feature, accompanied by a small blue-shift of the minimum of circa 30 meV.…”
Section: Transient Absorption Spectroscopymentioning
confidence: 83%
See 2 more Smart Citations
“…Additionally, a broad, minute positive amplitude was recorded for probe photon energies lower than 2.1 eV (600-750 nm, Figure S23), which builds up within the first ps. Previous studies attributed this spectral feature to the dissociation of excitons into electrons and holes with subsequent trapping of holes on the surface [46,68,69]. The subsequent behavior is characterized by the decay of the CdS bleach feature, accompanied by a small red-shift of the spectral position of the minimum of circa 50 meV, and the decay of the CdSe bleach feature, accompanied by a small blue-shift of the minimum of circa 30 meV.…”
Section: Transient Absorption Spectroscopymentioning
confidence: 83%
“…For the range 530-630 nm (indicating changes in excited CdSe), two time constants and an offset were needed for DHLA-and DHLA-PEG-NR, and three and an offset for TOPO-NR, MUA-NR, and HS-PEG-NR, and PEI-NR. Parallel to the initial CdS and CdSe bleach formation processes formation of a broad positive amplitude for probe photon energies lower than 2.1 eV ( Figure S23), indicative of surface trapping of holes [46,68,69], is observed. This process exhibits a minor ligand-dependence: for all thiol-based ligands, the risetime is in the order of 0.3 ps and below, while TOPO-and PEI-NR exhibit slightly higher risetimes (0.8 and 0.5 ps, respectively).…”
Section: Transient Absorption Spectroscopymentioning
confidence: 88%
See 1 more Smart Citation
“…We found that trapped holes on the surfaces of CdS nanorods are not stationary on the time scale of electron–hole recombination but instead undergo a diffusive random walk on the particle surface . In this Perspective, we summarize our experimental and theoretical efforts to understand the motion of surface-trapped holes in CdS and CdSe nanocrystalline materials. We first describe how transient absorption (TA) spectroscopy experiments and theoretical modeling of NCs with a unique morphology led to the observation of trapped-hole diffusion. We then summarize insights into the mechanism of hole hopping from theory, computations, and TA experiments in multiple materials recorded over a range of temperatures and time scales.…”
mentioning
confidence: 99%
“…Our dominant observation is that the modulation beam affects the slope of the ON probability distribution, leaving the OFF-state behavior unaltered. We considered the possibility that this effect arose from additional excitations into the absorption tail, either phonon-assisted band-to-band transitions or to surface-directed shallow defect states that may interconvert with the relaxed exciton. However, a slope change has not been reported for intensity-dependent studies with conventional supra-gap excitation, , which disfavors a straightforward effect from additional ground-state photoexcitations. Moreover, we expect that this additional flux of excitations from the modulation laser is small relative to the excitation rate from the λ: 470 nm laser.…”
mentioning
confidence: 99%